PEMANFAATAN TUMBUHAN OBAT DI KECAMATAN BUNAKEN, KOTA MANADO, PROVINSI SULAWESI UTARA - Johandi R. Lingkubi; Maria Y.M.A. Sumakud; Wawan Nurmawan; Euis F.S. Pangemanan (COCOS, 2015)
ABSTRACTThe use of plants as medicine from generation to generation by the local people. The aims of this study is to determine the types and how to use the medicin plants by the community. The research was conducted in the District of Bunaken, Manado, North Sulawesi. The method of this research was interviewing traditional doctors in the study area. Data were analyzed descriptively. Based on this research, there are 35 species consist of 22 families of plants. The parts was used were leaves, stems, all parts, rhizomes, roots, sap, fruit, flowers, buds, petiole, and tubers, they used by boiled direct, direct used, herbal and drink.Key Words : Plant Medicine, Local People, District of Bunaken